GEOSPATIAL DISTRIBUTION OF FOREST SPECIES IN THE BOTANICAL GARDEN OF RECIFE, PERNAMBUCO, BRAZIL - Almeida, Débora de Melo; Freire, Fernando José; da Silva, Marcos Vinícius; Barbosa, Uilian do Nascimento; Cavalcante, Douglas Monteiro; Silva, Emanuel Araújo (Floresta, 2023)
The adoption of appropriate strategies for the conservation and management of forest ecosystems associated with the Atlantic Forest depends on understanding the pattern of spatial distribution of forest species, mainly in protected areas. Thus, this study aimed to evaluate the geospatial distribution of forest species in a fragment of Atlantic Forest (Lowland Dense Ombrophilous Forest) in the Botanical Garden of Recife, Pernambuco, Brazil. The phytosociological study was carried out by the plot method, with 40 plots of 10 m x 25 m, systematically distributed, where all living individuals that showed circumference at 1.3 m above the ground ≥ 15 cm were identified and georeferenced. To identify the existence of floristic similarity between the plots, the obtained data were subjected to hierarchical cluster analysis. The spatial variability of forest species was characterized using geostatistical analysis. The data were interpolated by kriging, followed by the construction of thematic maps of spatial distribution. Hierarchical cluster analysis revealed the formation of two groups of plots. The forest species Artocarpus heterophyllus, Dialium guianense, Helicostylis tomentosa, Hevea brasiliensis, Pouteria durlandii and Thyrsordium spruceanum showed spatial dependence. The use of geostatistics allowed visualizing the spatial distribution arrangements and identifying the concentration sites of these species. Information on the geospatial distribution of forest species can be used for the preservation, conservation and management of forest remnants.